IoT Innovations: Sensors Integration and Communication for Smart Environments Journal - B.M. Rajesh; Monisha S.; Jayasree T. (International Journal of Wireless Security and Networks, 2024)
In today’s rapidly advancing technological landscape, companies are racing to embrace the transformative concept of the Internet of Things (IoT), merging physical objects with the vast realm of the internet. This integration, facilitated by smart hardware and software, promises a seamless network where objects communicate and actively engage in our daily lives. However, the journey to this interconnected future is not without hurdles. Addressing the myriad challenges from diverse perspectives is crucial to unlock the full potential of IoT. While this evolution holds the promise of revolutionizing traditional lifestyles into more sophisticated and interconnected experiences, overcoming these obstacles remains a critical step in achieving this vision. This comprehensive review paper aims to furnish readers with an in-depth exploration of IoT, delving into its multifaceted dimensions from both technological and societal viewpoints. It meticulously examines the diverse challenges and issues inherent in IoT, elucidating its definition and architectural intricacies. Moreover, it meticulously outlines various sensors and actuators, shedding light on their intelligent communication mechanisms. Additionally, it highlights pivotal application areas where IoT stands to make a profound impact. By offering this detailed analysis, the paper endeavors to equip readers and researchers with a profound understanding of IoT and its far-reaching potential in real-world applications.
Keywords: Internet of things (IoT); actuators; and smart communication integrating systems network interface for smart homes and cities; sensors